Case Report: SMARCA4-deficient NSCLC with brain metastasis harboring co-mutations in chromatin remodeling and DNA damage repair pathways - Song, Jiaqin; Yang, Shikun; Xia, Lei (Frontiers in Oncology, 2025)
SMARCA4 (SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily A member 4) is the core ATPase subunit of SWI/SNF chromatin remodeling complexes. Its deficiency constitutes a rare and aggressive subtype of non-small cell lung cancer (SMARCA4-DNSCLC) characterized by rapid progression, propensity for early metastatic dissemination, and dismal prognosis (median overall survival: ~6 months). Notably, SMARCA4 mutations demonstrate significant co-occurrence with DNA damage repair (DDR) pathway dysregulation, though the clinical implications and molecular interplay of these co-mutations remain poorly understood. We present a treatment-naïve SMARCA4-DNSCLC case with synchronous brain metastasis harboring a unique genomic profile: concurrent mutations in chromatin remodeling genes (SMARCA4, CHD8, NSD1) and DDR pathway genes (ATR, BARD1, TP53), accompanied by elevated tumor mutational burden (TMB-H). This molecular signature implies potential synergistic effects between chromatin instability, compromised DNA damage repair mechanisms, and augmented immunogenicity. Through comprehensive genomic analysis, we elucidate the biological significance of this mutational landscape and discuss its therapeutic implications, aiming to advance precision diagnosis and guide innovative treatment strategies for SMARCA4-DNSCLC.